Case report and literature review: Robot-assisted laparoscopic left renal mucinous cystadenocarcinoma radical nephrectomy - Ning, Zikuan; Zhang, Haoxun; Wang, Bowen; Wang, Yingwei; Liu, Yiwen; Tao, Boju; Zhang, Guoling; Liu, Hua; Wang, Chunyang (Frontiers in Surgery, 2023)
Background Mucinous cystadenocarcinoma (MC) of the kidney is a rare renal epithelial tumor originating from the renal pelvic urothelium. There are only a few published reports on MC. Due to its rare and unknown tissue origin, its diagnosis is difficult which almost can be diagnosed through the pathological method. Case presentation In this case report, we report a female patient whose chief complaint was low back pain lasting for one month. The three-dimensional computed tomography scan of the urinary system detected approximately 7 cm of a left renal cystic mass. The renal cystic mass was diagnosed as MC after robot-assisted laparoscopic radical nephrectomy. The MC originated from the kidney after completing colorectal adenocarcinoma and ovarian adenocarcinoma. Conclusions We reported a case of MC of the kidney which was a rare renal tumor. We not only aimed to present an unusual case of MC and review the previous literature on its pathology and differential diagnosis, but also used new method to treat this type of tumor.